2018
DOI: 10.1002/star.201700270
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel 2D Composites of Silk Sericin and Rice Starch and Application as Bio‐Compatible Scaffold for Cell Culturing

Abstract: Sericin and starch are waste materials of the silk and rice milling industries, respectively. Owing to their suitable physicochemical, mechanical and functional properties, the two materials are thermo‐mechanically conjugated and cast as films. Sericin forms a microfibrillar network structure which binds with gelatinized starch. Addition of crosslinkers, namely glycerol and polyethylene glycol results in smoother textured films, higher crystallinity, and thermal resistance as studied using XRD, FTIR, DSC, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Further molecular displacement in low-molecular-weight poly­(ethylene glycol) (PEG) reduced water content and improved the tolerance temperature to the range of −70 to 120 °C. Enhanced antifreezing heat-resistant performances of SA hollow hydrogel tubes as well as their increased flexibility are achieved by the treatments in glycerol and PEG. , All details of the preparation of SA hollow hydrogel tubes and their functionalization for enhanced antifreezing heat-resistant performances, as well as the potential applications as carriers, are demonstrated and discussed. We report this new method for the creation of nontoxic, antifreezing heat-resistant hollow hydrogel tubes that may find promising applications in various extreme temperature environments in biomedical fields.…”
Section: Introductionmentioning
confidence: 99%
“…Further molecular displacement in low-molecular-weight poly­(ethylene glycol) (PEG) reduced water content and improved the tolerance temperature to the range of −70 to 120 °C. Enhanced antifreezing heat-resistant performances of SA hollow hydrogel tubes as well as their increased flexibility are achieved by the treatments in glycerol and PEG. , All details of the preparation of SA hollow hydrogel tubes and their functionalization for enhanced antifreezing heat-resistant performances, as well as the potential applications as carriers, are demonstrated and discussed. We report this new method for the creation of nontoxic, antifreezing heat-resistant hollow hydrogel tubes that may find promising applications in various extreme temperature environments in biomedical fields.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have also explored the interaction between starch and protein from other different perspectives (Espinosa-Dzib, Ramírez-Gilly, & Tecante, 2012;Homer, Kelly, & Day, 2014;Ravindra, Genovese, Foegeding, & Rao, 2004). Dutta reported that silk sericin and rice starch can be thermo-mechanically conjugated and casted into continuous 2D films through evident molecular interaction between starch and sericin (Dutta, Dutta, & Devi, 2018). Both starch, protein, and their interaction are responsible for the macroscopic properties of food matrix (Jekle et al, 2016).…”
mentioning
confidence: 99%